Developing critical cultural competence : a guide for 21st-century educators - Cooper, Jewell E. (Corwin Press, 2011)
This work outlines a professional development programme to raise staff's cultural competence to teach diverse students. Teachers can increase understanding of themselves, their students, and their families.